EFEKTIVITAS PENGGUNAAN QUIZIZZ UNTUK MENINGKATKAN MINAT BELAJAR MATEMATIKA PADA PEMBELAJARAN DARING MAHASISWA DI KABUPATEN POHUWATO - Muliani Muliani; Darmawati Darmawati (Delta: Jurnal Ilmiah Pendidikan Matematika, 2022)
Research on the use of Quizizz media has been carried out by several researchers, but has a different object. This study will focus on the interest in learning mathematics in online learning of students in Pohuwato Regency. The focus of this research is based on the problem of the lack of interest in learning mathematics in Pohuwato Regency, especially when online learning began to be applied during the Covid-19 pandemic. o overcome this problem, it is necessary to have an online learning support media in the form of Quizizz which is integrated with the online learning model of blended learning that focuses on independent learning, namely the flex model that can effectively increase students' interest in learning mathematics. This study aims to determine the effectiveness of using Quzziz integrated with the flex model in increasing interest in learning mathematics in online learning. The research method used in this study is a pre-experimental design with a one-group pretest-posttest design model. The results of the pre-test and post-test have a positive correlation of 0,920 = 92%, the value of sig. = 0,000 < 0,050 and a positive value of t-count = -31,770 > t-table = 2,101 based the conclusion that H0 is rejected and Ha is accepted so that the use of quizizz  integrated flex model is effective in increasing interest in learning mathematics in online learning of students in Pohuwato Regency.